2019
DOI: 10.2147/cmar.s191712
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dynamic impact of inflammation-based indices in colorectal cancer patients receiving FOLFOX-based chemotherapy</p>

Abstract: Background: Inflammatory cellular response is implicated in the pathogenesis of colorectal cancer (CRC). Nevertheless, the dynamic effects of inflammatory index coNLR (neutrophil-to-lymphocyte ratio)-PLR (platelet-to-lymphocyte ratio) during chemotherapy remain elusive. Methods: The baseline clinical data and laboratory parameters of 480 CRC patients who received palliative resection of primary tumors and FOLFOX-based chemotherapy from January 2007 to January 2013 were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Inflammation is involved in multiple different stages of tumor development, including the initiation, promotion and migration (40,41). In previous studies, the expression levels of COX-2 were reported to be significantly overexpressed in patients with glioma, positively correlated with glioma malignancy and negatively correlated with prognosis (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is involved in multiple different stages of tumor development, including the initiation, promotion and migration (40,41). In previous studies, the expression levels of COX-2 were reported to be significantly overexpressed in patients with glioma, positively correlated with glioma malignancy and negatively correlated with prognosis (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, continuous inflammatory stimulation can lead to chronic inflammation, poor tissue regeneration, tumorigenesis, and metastasis [5]. Pro-inflammatory cytokines are released by tumor-associated inflammatory cells, such as IL-1, IL-6, TNF, and VEGF, which further influences the tumor progression and metastasis [6,7]. Besides, inflammation has an osculating link with the development and malignant progression of most cancers by regulating DNA damage and repair, p53 mutation, chemokines, and soon [8].…”
Section: Introductionmentioning
confidence: 99%